Retention and Transfer of Fractal Gait Training - Logan J. Frame; Nikita A. Kuznetsov; Louisa D. Raisbeck; Christopher K. Rhea (Biomechanics)
Background/Purpose: Fractal gait patterns have been shown to be modifiable, but the extent to which they are retained and transferred to new contexts is relatively unknown. This study aimed to close those gaps by enrolling participants (N = 23) in a seven-day fractal gait training program. Methods: Building on related work, the fractal gait training occurred on a treadmill over a 10-min period. Before and after the treadmill training, each participant walked for 10 min overground without the fractal stimulus used during training. The daily post-test was used to examine immediate retention and transfer of the fractal gait patterns from the treadmill to overground. The pre-tests in days 2–7 were used to examine the extent to which the fractal gait patterns from the preceding day were retained 24 h later. Inertial measurement units were used to measure stride time so a consistent measurement method could be employed in the treadmill and overground phases of the study. Results: Our results showed that multiple days of treadmill training led to elevated fractal patterns, indicating a positive training effect. However, the positive training effect observed on the treadmill did not transfer to overground walking. Conclusions: Collectively, the data show that fractal patterns in gait are modifiable across multiple days of training, but the transferability of these patterns to new contexts needs to be further explored.